2022
DOI: 10.15252/embj.2022111289
|View full text |Cite
|
Sign up to set email alerts
|

Selective autophagy of RIPosomes maintains innate immune homeostasis during bacterial infection

Abstract: The NOD1/2‐RIPK2 is a key cytosolic signaling complex that activates NF‐κB pro‐inflammatory response against invading pathogens. However, uncontrolled NF‐κB signaling can cause tissue damage leading to chronic diseases. The mechanisms by which the NODs‐RIPK2‐NF‐κB innate immune axis is activated and resolved remain poorly understood. Here, we demonstrate that bacterial infection induces the formation of endogenous RIPK2 oligomers (RIPosomes) that are self‐assembling entities that coat the bacteria to induce NF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 65 publications
0
7
0
Order By: Relevance
“…39 This study also reported direct interaction of RIPosomes, and also of NOD receptors and RIPK2, with the autophagy factor immunity-related GTPase M protein that negatively regulates inflammation mediated by RIPK2. 39 2.3. RIPK2 Phosphorylation and Ubiquitination.…”
Section: Ripk2: Structure Expression and Signaling Pathwaysmentioning
confidence: 57%
See 1 more Smart Citation
“…39 This study also reported direct interaction of RIPosomes, and also of NOD receptors and RIPK2, with the autophagy factor immunity-related GTPase M protein that negatively regulates inflammation mediated by RIPK2. 39 2.3. RIPK2 Phosphorylation and Ubiquitination.…”
Section: Ripk2: Structure Expression and Signaling Pathwaysmentioning
confidence: 57%
“…RIPK2 polymerization is an essential process for activation of the NF-κB and MAPK inflammatory signaling pathways and downstream induction of pro-inflammatory cytokines such as interleukin-6 (IL-6), tumor necrosis factor-α (TNF-α), and IL-12/23p40. ,, A recent study showed that activation of the NF-κB inflammatory pathway by pathogenic bacteria led to formation of oligomeric RIPK2 structures termed “RIPosomes” . This study also reported direct interaction of RIPosomes, and also of NOD receptors and RIPK2, with the autophagy factor immunity-related GTPase M protein that negatively regulates inflammation mediated by RIPK2 …”
Section: Ripk2: Structure Expression and Signaling Pathwaysmentioning
confidence: 80%
“…We showed that upon Irgm1 depletion, the cGAS-STING-IRFs and NODs-RIPK2-NFκB signaling are activated to induce type 1 IFN response (Jena et al, 2020; Mehto et al, 2022). We next examined whether type 1 IFN response is responsible for protective phenotypes observed in hACE2; Irgm1 −/− mice by inhibiting the STING and RIPK2 ( Supplementary Figure 8A and 8G ).…”
Section: Resultsmentioning
confidence: 99%
“…GSK583 is a potent inhibitor of RIPK2 and can suppress NF-κB response. Recently, we found that GSK583 could suppress NF-κB-dependent interferon and cytokine response in IRGM-depleted human cells and Irgm1 −/− mice (Mehto et al, 2022). GSK583 treated hACE2; Irgm1 −/− mice ( Supplementary Figure 8G ) showed clinical symptoms similar to hACE2 mice indicating suppression of protective effects ( Supplementary Figure 8H ).…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, RIPK2 can activate the autophagy and suppress reactive oxygen species (ROS) production (Gao et al 2019 ; Lupfer et al 2014 ), which was intimately linked to the kinase activity of RIPK2 itself (Lupfer et al 2013 ). RIPK2 self-assembled endosome or RIPosome provide a signal of being eaten in the process of autophagy (Irving et al 2014 ; Mehto et al 2022 ), this may serve as a scavenger to eliminate ROS in cells. We and other groups have previously shown that increased ROS production can trigger pancreatic cancer cell apoptosis (Lee et al 2022 ; Wang et al 2021 ).…”
Section: Discussionmentioning
confidence: 99%